Alterations in innate and adaptive immune leukocytes are involved in paediatric obesity - Inzaugarat, Maria Eugenia (2013)
Background: Adipose tissue is the main source of the cytokines and adipokines that are increased in the context of obesity. The production of reactive oxygen species (ROS) and cytokines by circulating immune cells can be regulated by these pro-inflammatory factors even before infiltration into adipose tissue. Objective: To investigate the alterations that can occur in circulating monocytes and lymphocytes in paediatric obesity. Methods: In this study, 54 paediatric obese patients and 30 age-matched metabolically healthy individuals were enrolled. Intracellular cytokines were analyzed after phorbol myristate acetate (PMA) or leptin plus PMA stimulation of lymphocytes and monocytes by flow cytometry. ROS generation was measured using dichlorofluorescein-diacetate. Both a 'stimulation index' and a 'fold of increase' were calculated for statistical purposes. Results: Both interferon gamma (IFN-γ) production by circulating CD4+ and CD8+ lymphocytes and ROS production by monocytes following PMA stimulation were increased in obese patients. Leptin induced an increased production of IFN-γ in both subsets of T cells and tumour necrosis factor alpha in monocytes, and linoleic acid induced a higher ROS production in monocytes. Conclusions: The distinct functional responses of circulating cells suggest that alterations in both innate and adaptive immune cells are involved in the maintenance of low-grade inflammation in paediatric obesity.